Factors That Influence the Performance of Class II Fish Auction in Pati Regency - Herna Octivia Damayanti; Suradi Wijaya Saputra; Dian Wijayanto; Abdul Kohar Mudzakir (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
The Fish Auction Place has a function as a marketing place for fishermen’s catches through the auction process. The auction activities carried out by the Class II TPI in Pati Regency showed that the performance was not optimal. The purpose of this research was to analyze the factors that influence the performance of class II fish auctions place in the Pati Regency. The research locations were the Banyutowo Fish Auction Place and the Puncel Fish Auction Place. Research time was held from January to October 2021. The number of research samples was 110 respondents. Data analysis with Structural Equation Modeling with AMOS software. The results showed that the factors that influence the performance of class II fish auctions place were planning, organizing, actuating, and controlling. These four variables have a positive and significant effect on the performance of class II fish auctions placed in the Pati Regency. The driving factor has the greatest influence on the performance of class II fish auctions in the Pati Regency with a standard regression coefficient value of 0.365. If actuating is getting better, the achievement of performance indicators was higher. On the other hand, if actuating gets weaker, the achievement of performance indicators was lower. Thus, the actuating factor needs to get greater attention in the management of the class II fish auction place in Pati Regency.